2020
DOI: 10.1101/2020.11.02.362517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downstream of gasdermin D cleavage, a Ragulator-Rag-mTORC1 pathway promotes pore formation and pyroptosis

Abstract: The process of pyroptosis is mediated by inflammasomes and a downstream effector known as gasdermin D (GSDMD). Upon cleavage by inflammasome-associated caspases, the N-terminal domain of GSDMD forms membrane pores that promote cytolysis. Numerous proteins are recognized to promote GSDMD cleavage, but none are known to be required for pore formation after GSDMD cleavage. Herein, we report a forward genetic screen that was designed to identify regulators of pyroptosis that act downstream of GSDMD cleavage. This … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…This suggests to us that beyond their intrinsic resistance to pyroptosis (e.g. ESCRT machinery, Caspase-1 expression levels, Ragulator pathway…) (Bjanes et al, 2021;Chen et al, 2018;Evavold et al, 2020;Rühl et al, 2018), neutrophils might have additional factors that restrict the ability of bacteria to promote NLRC4-dependent pyroptosis. Related to this, a seminal study from Zynchlynsky and colleagues found that neutrophil serine proteases could degrade the Type-3 Secretion System and flagellin virulence factors of S. flexneri (Weinrauch et al, 2002), hence limiting their ability to hijack the neutrophil autonomous immunity and restraining Shigella-induced neutrophil necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests to us that beyond their intrinsic resistance to pyroptosis (e.g. ESCRT machinery, Caspase-1 expression levels, Ragulator pathway…) (Bjanes et al, 2021;Chen et al, 2018;Evavold et al, 2020;Rühl et al, 2018), neutrophils might have additional factors that restrict the ability of bacteria to promote NLRC4-dependent pyroptosis. Related to this, a seminal study from Zynchlynsky and colleagues found that neutrophil serine proteases could degrade the Type-3 Secretion System and flagellin virulence factors of S. flexneri (Weinrauch et al, 2002), hence limiting their ability to hijack the neutrophil autonomous immunity and restraining Shigella-induced neutrophil necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…recently uncovered the Ragulator/Rag/mTORC pathway in a genetic screen for factors required in GSDMD-dependent pore formation (87). Intriguingly, the Ragulator complex acts downstream of GSDMD but upstream of NINJ1-induced cell lysis, as Rag was required for pore formation, whereas NINJ1 acts subsequent to pore formation to induce membrane rupture and ultimate cytolysis (40, 87). As Card19 -/- macrophages exhibit a kinetic delay and reduced overall amplitude of pore formation, our findings suggest that the factor responsible acts at a similar step to the Ragulator complex, and upstream of NINJ1 to facilitate pore formation prior to terminal cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to identification of NINJ1 as a regulator of cell lysis, Evavold et al recently uncovered the Ragulator/Rag/mTORC pathway in a genetic screen for factors required in GSDMD-dependent pore formation (86). Intriguingly, the Ragulator complex acts downstream of GSDMD cleavage but upstream of NINJ1-induced cell lysis, as Rag was required for pore formation, whereas NINJ1 acts subsequent to pore formation to induce membrane rupture and ultimate cytolysis (41,86). Thus, in contrast to initial models proposing that release of the N-terminal portion of GSDMD was necessary and sufficient to trigger cell lysis, these findings collectively support a multi-step regulated process, downstream of GSDMD cleavage, that ultimately triggers lytic rupture of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…During pyroptosis, GSDMD pore formation is typically followed by the loss of mitochondrial function ( 42 ), cell ballooning ( 42 ) and finally cell rupture (all discussed below). GSDMD-NT translocated to the plasma membrane in RagA-deficient cells but maintained membrane permeability (measured by propidium iodide (PI) uptake), mitochondrial function, and cell morphology, suggesting a role of the Ragulator-Rag complex in GSDMD pore formation itself and not in other, downstream events leading to cell death ( 41 ). It remains to be investigated whether any component of the Ragulator-Rag-mTORC1 pathway directly binds to GSDMD-NT to support oligomerization or if an intermediate interaction partner exists that exerts this action.…”
Section: Gasdermin Pore Formation Repair and Cell Lysis Are Distinct And Regulated Eventsmentioning
confidence: 99%
“…Once at the membrane, the N-terminal fragments oligomerize, in a process dependent on a cysteine residue at position 192 in humans (Cys191 in mice), to form a functional pore (39). An elegant genetic screen by Evavold et al (41), designed to identify regulators of pyroptosis downstream of GSDMD cleavage, showed that the GSDMD oligomerization is not a passive event but is regulated downstream of the Ragulator-Rag complex, typically known for its metabolic control of mTORC1 pathway. The components of the Ragulator-Rag complex, such as RagA or RagC, were dispensable for GSDMD trafficking to the cell membrane, but were essential for GSDMD-NT oligomerization and pore formation.…”
Section: Gasdermin Pore Formationmentioning
confidence: 99%